(untitled) (Fiep Bulletin - online, 2019)
The formation and development of the Normal Schools (EN) as training of professionals in education, occupies aprivileged place in the agenda of educational and social development, because it aspires to train the best teachers in the country.From this perspective, the Bachelor in Physical Education (LEF) seeks to update and deepen the knowledge and scientific skillsof students in a self-directed and permanent manner, which contributes to the improvement of educational practice; Hence, in thepresent investigation, the first phase of the study is considered to answer the central question: What are the epistemologicalbeliefs held by the first-grade students of the LEF of the BENV "ECR", in the school year 2017- 2018, facing the concept oflearning and the needs of the teaching practice of the Current Educational System ?; from analyzing and describing thedimension called Structure of Knowledge proposed by Schommer-Aikins, obtaining as conclusions that the epistemologicalbeliefs of the LEF students influence the structure of knowledge and influence the teaching-learning process; so that theinvestigation of the epistemological beliefs and their effects should continue to be investigated in the NES which generatesreflexive, critical and self-directed students in the exercise of their teaching and personal training.